Stent-alone treatment of unruptured vertebral artery fusiform aneurysms: A comparison of flow diverter and conventional stents - Li, Wenqiang; Zhu, Wei; Wang, Yanmin; Zhao, Yapeng; Wang, Yang; Liu, Xianzhi; Zhang, Yisen (Frontiers in Neurology, 2022)
Background Treatment of vertebral artery fusiform aneurysms (VAFAs) is complex and controversial. This study aimed to compare the safety and efficacy between flow diverter and conventional stents in patients with VAFAs undergoing endovascular stent-alone treatment (SAT). Methods Thirty-six patients with 36 VAFAs who underwent SAT between January 2014 and December 2018 were retrospectively analyzed. Patient and aneurysm characteristics, procedural details, complications, and angiographic and clinical outcomes were compared between flow diverter stent patients (n = 22) and conventional stent patients (n = 14). Results More branches covered with stent were found in the conventional stent group (88.9 vs. 33.3%; p = 0.008). The number of stents placed was significantly higher in the conventional stent group (1.57 ± 0.76 vs. 1.09 ± 0.29; p = 0.016). The proportion of patients with significant or moderate stasis within the aneurysm immediately after stent placement was higher in the flow diverter stent group (95.5 vs. 57.1%; p = 0.004). The proportion of patients with complete obliteration or only a residual neck on follow-up angiography was significantly higher in the flow diverter stent group (86.3 vs 50.0%; p = 0.047). However, the incidence of parent artery stenosis or occlusion was also higher in the flow diverter stent group (27.3% vs. zero; p = 0.032). The rate of complications did not significantly differ between the groups. Conclusions SAT was safe and effective in patients with VAFAs. Flow diverter stents are associated with a significantly better complete occlusion rate than conventional stents; however, they are also associated with an increased risk of parent artery stenosis.